U.S. Countervailing Duty Law and the WTO Rules for Subsidies: the Issue of Consistency - Zvenyslava Opeida (Lex Portus, 2019)
he paper focuses on U.S. law regulating countervailing measures. It examines two substantive elements which must be established in order to impose countervailing measures: (1) the imports are benefiting from countervailable subsidy, and (2) the subsidized imports cause material injury to a U.S. industry. The procedure of countervailing duty investigation is also reviewed, including such stages as filing petition and initiation of investigation, preliminary subsidy and injury determination, final subsidy and injury determination, and appeals. The possible remedies that include the imposition of CVDs (provisional and definitive duties) or a suspension agreement are also characterized. Special attention is given to the issues of U.S. law and practice consistency with the World Trade Organization (WTO) rules on subsidies. A number of WTO Dispute Settlement Body’s decisions regarding the consistency of the CVDs adopted by the United States with WTO law are also examined.